The built environment, cognition and the image: towards an architectural epistemology - Volpe, Stephanie (School of Architecture, Planning and Geomatics, 2020)
Man is increasingly assuming conscious control over his physical environment. The impact of rapidly accelerating scientific and technological progress has resulted in the environment being increasingly man-made and man-influenced. The growing urban population has necessitated building at a rate and quantity greater than ever before. Enormous resources, both human and material, are being channelled on an unprecedented scale into the planning, designing and construction of new environments for human use. Whilst this tide of energy and activity continues to surge forward, creating vast urban and suburban. developments, very little energy and resources have, by comparison, been directed towards critically assessing the impact that these built environments have on people, and the extent to which they are responsive to human needs and aspirations. It has become critical for the architect to be made fully aware of the human implications of the physical environment he is creating. Concern for the human element has been eclipsed by the current pre-occupation of the design profession with technology and economics which have become the dominant design imperatives.